METAMORPHOSIS OF THE SCIENTIFIC JOURNAL: PAST, PRESENT AND FUTURE - Jange, Suresh; Kademani, B.S. (Malaysian Journal of Library and Information Science, 1999)
Describes how the scientific journal has undergone changes over a period of time from print medium to electronic form, as an innovative medium for communicating scientific literature. With the advance of science and technology, information grew and related technology emerged from long letters containing primary literature in 16th century to electronic database, online hosts etc. The electronic journal offers a faster method of disseminating information with effective retrieval efficiency and its capability to hold large amount of information in compact form. Further explores the importance of electronic journal, its growth and the key issues regarding its progress. The paper concludes with a remark on the part of librarian and information officers in handling the electronic journals weighing all the possible alternatives while keeping in view the changing user needs.